Khadijah Binti Khuwailid Dan Perannya Dalam Perjuangan Rasulullah SAW - tunnaja08, safina (Maliki Interdisciplinary Journal, 2025)
This article discusses the role of Khadijah binti Khuwailid in the struggle of Prophet Muhammad SAW, particularly during the early years of the Islamic mission. As the first wife of the Prophet, Khadijah played a pivotal role in supporting and strengthening the Prophet’s spirit, both morally, emotionally, and materially. The article highlights Khadijah’s life journey, recognizing her as a noble, capable woman with extraordinary leadership qualities. Her courage, wisdom, and steadfastness in the face of challenges in spreading Islam laid a strong foundation for the continuation of the Prophet’s mission. Additionally, the article underscores Khadijah’s significant contributions to the early spread of Islam, at a time when the mission faced immense opposition and persecution from the Quraysh society. As a wealthy, influential, and respected woman, Khadijah not only stood by the Prophet during times of hardship but also provided substantial financial and moral support. Through her sacrifices, Khadijah set an exemplary model of unwavering faith, selfless devotion, and loyalty to the cause of Islam. This article aims to provide a deeper understanding of Khadijah’s essential role in Islamic history and to inspire Muslims to emulate the noble qualities she embodied.